The immunogenetics of multiple sclerosis. The frequency of HLA-alleles class 1 and 2 is lower in Southern Brazil than in the European population - Lineu Cesar Werneck; Paulo José Lorenzoni; Raquel Cristina Arndt; Cláudia Suemi Kamoi Kay; Rosana Herminia Scola (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective To study the HLA of class 1and 2 in a multiple sclerosis (MS) population to verify the susceptibility for the disease in the Southern Brazil. Methods We analyzed patients with MS and controls, by direct sequencing of the genes related to HLA DRB1, DQB1, DPB1, A, B and C alleles with high resolution techniques. Results We found a lower frequency of all HLA alleles class 1 and 2 in MS and controls comparing to the European population. Several alleles had statistical correlation, but after Bonferroni correction, the only allele with significance was the HLA-DQB1*02:03, which has a positive association with MS. Conclusions Our data have different frequency of HLA-alleles than the previous published papers in the Southeast Brazil and European population, possible due to several ethnic backgrounds.